2017
DOI: 10.1101/195644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomewide significant regions in 43 Utah high-risk families implicate multiple genes involved in risk for completed suicide

Abstract: Suicide is the 10th leading cause of death in the US. While environment has undeniable impact, evidence suggests that genetic factors play a major role in completed suicide. We have >4,500 DNA samples from completed suicides through a collaboration with the Utah Medical Examiner. We have linked the records from these cases to the Utah Population Database which includes multi-generation genealogies, demographic data, and medical information on over 8 million individuals. This linking has resulted in extended fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…The mood-related disorders category was defined so as to capture broader ICD codes that have been previously used to identify mental health conditions in prenatal populations. 13,[19][20][21][22][23] Medical conditions examined included epilepsy, multiple sclerosis, HIV/AIDS, hepatitis C, nausea, vomiting, and chronic pain. Outcomes were defined with codes established by the Centers for Medicare & Medicaid Services Chronic Conditions Data Warehouse and previous studies (eMethods in the Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…The mood-related disorders category was defined so as to capture broader ICD codes that have been previously used to identify mental health conditions in prenatal populations. 13,[19][20][21][22][23] Medical conditions examined included epilepsy, multiple sclerosis, HIV/AIDS, hepatitis C, nausea, vomiting, and chronic pain. Outcomes were defined with codes established by the Centers for Medicare & Medicaid Services Chronic Conditions Data Warehouse and previous studies (eMethods in the Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is a complex, multifactorial behavioral phenotype involving genetic predispositions and distal/proximal environmental factors. Family, twin, and adoption studies have established a genetic basis for suicidal behavior, with heritability of close to 50% (Coon et al, 2018;Dwivedi, 2012;Supriyanto et al, 2011). The search for biomarkers that help detect suicide risk in the early stages is valuable, highlighting the importance of studying suicide and psychiatric genetics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the genetic contribution to suicide is high. Recently, genotypes related to suicide have been revealed (42). According to a recent cohort study in Sweden, the heritability of completed suicide was found to be slightly higher in women than in men (40).…”
Section: Suicidementioning
confidence: 99%